PENGEMBANGA MODUL YANG DILENGKAPI MINDMAP PADA MATERI PROTISTA UNTUK SMA/MA - Enzi, Priska Pebri (Pendidikan Biologi, 2014)
This research is the development of the use of 4-D Models consisting of four stages namely, define, design , develop , and disseminate , but the study was only done until the development phase because limitations time and costs. Define phase consists of a front end analysis, the analysis of the student, and analysis tasks. At the design stage to design a module that is equipped to make mindmap on protists material to high school students. Then at some stage develop test the validity by a validator which consists of 2 professors and 2 STKIP PGRI Biology teacher SMAN I Painan. Test practicalities by 2 teachers and 30 students of class XI Science SMAN I Painan. Data were analyzed by using percentage and processed descriptively. The results of this study are generated mindmap module equipped on protists are very valid material with a value of 91.67%, which assessed the validity of the didactic aspects, construction, and technical. Then the resulting module is also included in the criteria is very practical with practical value by 93.83% teachers and practicality value by 86.75% students were assessed from the aspect of ease of use of the module, the benefits obtained, the efficiency of learning time. It can be concluded in the form of instructional media module equipped protists mindmap on material produced is very valid and very practical.